Mobile Banking Applications and Customer Satisfaction: Evidence from MAE Users - Haslindar Ibrahim; Rudresh Pandey; Riduwan Shah Kamarudin; Rayhani Syahlah M Radzi; Qiu Nuo; Quek Xin Ting; Shradda Chauhan; Sudiksha Swami; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
Mobile Banking a part of financial technologies commonly known as Fintech are getting prominent and capturing their market share rapidly in Malaysia. Fintech services which range from Mobile Banking, Internet Banking, e-Wallet Accounts, ATMs, Debit Credit Cards, Robo Advisers etc are a key concern for financial sector and almost all players of financial sector including Banks are either acquiring fintech application or trying to develop their own. Mobile Banking App MAE is a part of Internet Banking developed by Malayan Banking Berhad (Maybank) to support and acquire Fintech. This study investigates the impact of mobile banking app MAE towards customer satisfaction, focusing on the roles of perceived usefulness, perceived ease of use, and perceived security trust, A quantitative research design was employed, utilizing an online survey distributed to active MAE users, especially USM students. Data were collected from 150 respondents and were analyzed using descriptive statistics and regression analysis in SPSS to test the proposed hypotheses. Our findings reveal that, usefulness and ease of use are the main drivers of user satisfaction with the MAE mobile banking app.